2020
DOI: 10.1002/adfm.202001800
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Dopants with Intrinsic Counterion Separation Reveal the Effects of Electron Affinity on Dopant Intercalation and Free Carrier Production in Sequentially Doped Conjugated Polymer Films

Abstract: Carrier mobility in doped conjugated polymers is limited by Coulomb interactions with dopant counterions. This complicates studying the effect of the dopant's oxidation potential on carrier generation because different dopants have different Coulomb interactions with polarons on the polymer backbone. Here, dodecaborane (DDB)-based dopants are used, which electrostatically shield counterions from carriers and have tunable redox potentials at constant size and shape. DDB dopants produce mobile carriers due to sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(106 citation statements)
references
References 81 publications
(260 reference statements)
6
97
0
Order By: Relevance
“…The EPR results on the F 4 TCNQ-doped P3HT films therefore provide clear experimental evidence for interactions between the spins on the dopant and host, in agreement with the presence of Coulomb interactions between the hole on the semiconductor and dopant anions that has previously been proposed to be the cause of low mobilities observed in films doped with small molecular dopants such as F 4 TCNQ. 17,19,51 The estimated strength of the exchange interaction between spins on P3HT and F 4 TCNQ is smaller than typical values reported for π-stacked radicals, 37,38 in agreement with literature demonstrating that dopant anions in P3HT films are located within the alkyl side chain regions of P3HT crystallites rather than intercalated between the P3HT backbones. 25,29,52 In contrast to the observation of clearly different spectral signatures for BCF-and F 4 TCNQ-doped P3HT films by cw EPR, the echo-detected pulse EPR spectra appear almost identical for all dopant-solvent combinations and can be unequivocally assigned to the P3HT radical cation based on the proton ENDOR data.…”
Section: Discussionsupporting
confidence: 87%
“…The EPR results on the F 4 TCNQ-doped P3HT films therefore provide clear experimental evidence for interactions between the spins on the dopant and host, in agreement with the presence of Coulomb interactions between the hole on the semiconductor and dopant anions that has previously been proposed to be the cause of low mobilities observed in films doped with small molecular dopants such as F 4 TCNQ. 17,19,51 The estimated strength of the exchange interaction between spins on P3HT and F 4 TCNQ is smaller than typical values reported for π-stacked radicals, 37,38 in agreement with literature demonstrating that dopant anions in P3HT films are located within the alkyl side chain regions of P3HT crystallites rather than intercalated between the P3HT backbones. 25,29,52 In contrast to the observation of clearly different spectral signatures for BCF-and F 4 TCNQ-doped P3HT films by cw EPR, the echo-detected pulse EPR spectra appear almost identical for all dopant-solvent combinations and can be unequivocally assigned to the P3HT radical cation based on the proton ENDOR data.…”
Section: Discussionsupporting
confidence: 87%
“…The two dimensional Holstein model has already been successful in rationalizing various experiments carried out on semiconducting polymers. 27,30,35,[57][58][59]61 Using our model we can not only obtain quantitative agreement with experiments but also extract detailed information about the polaron coherence lengths, i.e, how far the hole delocalizes along the x and y directions in the 2D COF plane and through the columns (z directions). The full theoretical framework, including a description of the multiparticle basis set, expressions for the IR absorption spectrum, disorder, coherence functions, Coulomb binding, and the fundamental nature and origin of the IR peaks are discussed in detail in the Supporting Information.…”
Section: Theoretical Modelmentioning
confidence: 66%
“…In particular, defects arising from non-crystalline regions can trap the polarons, resulting in localization and subsequently yielding lower values of hole mobility and conductivity. The effects of domain size, 28,51 electronic defects, [52][53][54] crystallinity, 55,56 molecular weight, 33 side chain engineering, 57 and chemical dopants 30,35,58,59 have been previously discussed in the context of conjugated polymers. In all these cases, mid-IR polaron signatures have provided fundamental insights into local structure-property relationships and have successfully established key correlations between polaron coherence and hole mobility.…”
Section: Introductionmentioning
confidence: 99%
“…interaction in doped polythiophene films could be screened by using bulky dodecaborane clusters as the ptype dopant, leading to a high bulk hole mobility and electrical conductivity. 66,67 Liu et al explored the impact of electrostatic interaction on the doping efficiency in lightly n-doped fullerene derivatives with different dielectric constants (PCBM with ε r ≈3.7 and PTEG-1 with ε r ≈5.9). It was found that the doping efficiency of lightly doped PCBM layers was only a few percent, but doped PTEG-1 films exhibited a very high doping efficiency approaching 100%.…”
Section: Controlling the Electrostatics Of Counterionsmentioning
confidence: 99%